Pemanfaatan Sigil untuk Meningkatkan Keterampilan Guru dalam Mengembangkan Media Pembelajaran Berbasis Android - Ainil mardiyah; Radhya Yusri; Hafizah Delyana (Fakultas Sains Terapan, 2023)
Students' lack of motivation and independence to learn is a major factor in their low desire and interest in participating in the learning process. One form of Indonesia's rapid technological advancement is the use of smartphones. Moreover, smartphones are currently a very important necessity, even in the field of education, which has a huge impact and benefits on human life. Therefore, teachers play an important role in creating learning media by utilizing smartphone technology to support student learning activities. This training activity aims to prepare teachers to be more creative and innovative in developing teaching materials or learning media that use technology to motivate and facilitate students' learning at any time and from any location. The method used in this activity is by means of socialization and training, discussion, and questions and answers conducted at MTSN 1 Padang for MTSN 1 Padang teachers. Based on the activities carried out, the results obtained showed that the understanding and skills of teachers in making learning media using SIGIL software increased. As many as 75% of teachers are proficient in using SIGIL software to create e-modules that already contain audio, text, and video. So it can be concluded that the training provided is able to improve the knowledge and skills of teachers in designing digital-based teaching materials for the learning process.